Mean-square consensus of multi-agent systems with noise and time delay via event-triggered control. Issue 9 (June 2020) - Sun, Fenglan; Shen, Yunhao; Kurths, Jürgen; Zhu, Wei
Abstract: This paper studies the mean-square consensus for multi-agent systems with measurement noise and time delay via event-triggered control. By combining graph theory, stochastic analysis and matrix theory, some necessary and sufficient conditions for the consensus protocols are given. We show that through the periodic event-checking technique, the consensus systems could tolerate even a large time delay. Several simulations are presented to illustrate the effectiveness of the control protocol.